The Values of Islamic Education in The Maintenance of Bodies in Surau Gadang Village, Padang City - Putri Irmayanti, Azizah; Kustati , Martin; Amelia , Rezki; Syamsi , Syamsi; Maulana , Febrian (Jurnal Pendidikan Indonesia, 2023)
The organization of funerals is an integral part of the life of the Muslim community, and in Surau Gadang Village, aspects of Islamic education play a central role in guiding every stage of the process. This study aims to explore the form and implementation of the traditional tradition of death in Surau Gadang Village, as well as the values of Islamic education contained in it. This study used participatory observation methods and interviews to document the process of organizing funerals and analyze the values of Islamic education that color every step. These results are expected to make a positive contribution to the understanding and implementation of Islamic education values in everyday life, especially in the context of organizing Muslim community funerals in Surau Gadang Village, Padang City. The form and implementation of the traditional tradition of death in Surau Gadang Village is the gathering of the community of five tribes before the bathing process begins, using carano when bathing the corpse, wearing clothes and deta when lining the male corpse and wearing mukena when covering the female corpse, and carrying out the mayik maenvironment process before the body is brought to the grave.